Determining the Minimum Number of Ultrasound Simulations to Establish Competency. (October 2016) - Shanks, Anthony; Durst, Jennifer; Temming, Lorene; Colvin, Ryan
Abstract : Local Mentor: Eric Strand, MD APGO Advisor: Nancy Hueppchen, MD, MSc PURPOSE: To determine the number of simulations that are required to provide the novice learner with comparable ultrasound skills to a PGY1 Intern. BACKGROUND: There is renewed emphasis on training medical students prior to the start of residency. The VIMEDIX OB simulator offers the ability to simulate ultrasound images although the ideal integration into training is unknown. METHODS: Prospective cohort study of OB/GYN residents (n=33) and medical students entering OB/GYN residency (n=12). IRB approval was obtained prior to the start of the study. Each resident took a timed test on US image fetal biometry acquisition (head circumference, abdominal circumference and femur length). Accuracy and mean times (seconds) were established for PGY1, PGY2, PGY3 and PGY4 years. Medical students comprised the intervention cohort. The students performed timed growth scans after completing 1, 5, 10 and 15 simulations. Accuracy was then compared to PGY1, PGY2, PGY3 and PGY4 years. RESULTS: Thirty-three residents completed the study. Resident accuracy in obtaining satisfactory images for growth US decreased with advancing PGY year from 85.7% as a PGY 1 to 50% as a PGY4. Ten medical students completed all simulations for analysis. Accuracy was 41.7% after one simulation and 90.9% after 5. DISCUSSION: The use of an ultrasound simulator demonstrated that novice learners had to perform 5 simulations to demonstrate comparable growth scan accuracy to a PGY 1. Ultrasound accuracy decreased with advancing year in residency suggesting that skills should be maintained during training.